PENGARUH PERENCANAAN, KAPASITAS SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP PENYERAPAN ANGGARAN BELANJA DAERAH PADA PEMERINTAH KABUPATEN KEPULAUAN TALAUD - Alumbida, Deiby Isilda; Saerang, David P.E.; Ilat, Ventje (ACCOUNTABILITY, 2016)
The absorption of the budget is a very important part in the Government's financial management both central government or local governments, it isÂ  because the level of absorption of the budget can be used as an indicator of the extent of the commitment of the Government apparatus to manage the budget in accordance with the planning. Budgets which are absorbed based on planning will provide the maximum benefit to the good economy, is erabled encourage the improvement of welfare for the area which is one of the nation's national goal of Indonesia. This research was conducted in the Talaud Islands Regency with the purpose of analyzing the influence of planning, capacity of human resources and organizational commitment toward regional budget absorption rate either simultaneously or partial. This research uses 3 independent variables consist of Planning (X1), Human Resource Capacity (X2), Organizational Commitment (X3) the dependent variable is the Absorption Of The Budget (Y). Data analysis was endured by using multiple linear regression analysis. The results indicates that the planning, capacity of human resources and organizational commitment affect the absorption of the regional budget of Talaud Islands Regency Government. However, only partially significantly influence planning while the capacity of the human resources and the commitment do not significantly influence the absorption of budget. Multiple linear regression analysis results show the planning, human resource capacity and commitment of the organization have a positive effect to the absorption of the budget. While the results of the analysis show that the determination of the coefficient of 36.2% absorption rate is affected by the budget planning, capacity of human resources and organizational commitment onthe other hard 63.8% absorption rate is influenced by other variables which are not included in this research. Keywords : Teori Institusional, Teori Pengabdian, Social Learning Theory